Global Exposure -- SMU Infographics - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Before your plane takes off, there is seemingly endless research and planning to be done. Our global exposure infographic is filled with must-have survival tips and fun facts to keep your planning and travelling stress free. Download or share it with your travel buddies today!